2014
DOI: 10.1016/j.pain.2014.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging contribution for diagnosing symptomatic neurovascular contact in classical trigeminal neuralgia: A blinded case-control study and meta-analysis

Abstract: Although classical trigeminal neuralgia (CTN) is frequently caused by neurovascular contact (NVC) at the trigeminal root entry zone (REZ), both anatomical and MRI studies have shown that NVC of the trigeminal nerve frequently occurs in individuals without CTN. To assess the accuracy of MRI in distinguishing symptomatic from asymptomatic trigeminal NVC, we submitted to high-definition MRI the series of CTN patients referred to our outpatient service between June 2011 and January 2013 (n=24), and a similar numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
103
2
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(139 citation statements)
references
References 55 publications
8
103
2
13
Order By: Relevance
“…Previous studies using MRI have demonstrated that neurovascular compression without atrophy is common even in asymptomatic individuals, but the presence of atrophy is much more likely to be associated with symptoms. 1,15,18 Pathological analysis of nerve specimens obtained at surgery have demonstrated clear histological and ultrastructural changes in the symptomatic trigeminal nerve, including focal demyelination and axonal loss, which seem to be correlated with the severity of vascular compression. 3,6,12 These changes might lead to alterations in conduction that lead to the development and progression of TN symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using MRI have demonstrated that neurovascular compression without atrophy is common even in asymptomatic individuals, but the presence of atrophy is much more likely to be associated with symptoms. 1,15,18 Pathological analysis of nerve specimens obtained at surgery have demonstrated clear histological and ultrastructural changes in the symptomatic trigeminal nerve, including focal demyelination and axonal loss, which seem to be correlated with the severity of vascular compression. 3,6,12 These changes might lead to alterations in conduction that lead to the development and progression of TN symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,13,21 Structural changes in the trigeminal nerve, leading to volume loss, have been well documented, 3,6,12 and a number of studies have demonstrated that nerve atrophy ipsilateral to the symptomatic side is visible on preoperative MRI. 1,4,5,7,9,15,17 Recently, Leal et al demonstrated that atrophy in the midcisternal region of the nerve is associated with more severe vascular compression, and these patients tend to exhibit greater clinical improvement following surgical decompression of the nerve. 10 However, it is unclear whether the nerve atrophy is entirely due to physical compaction by the compressing vessel or whether it is due, in part, to irreversible structural changes.…”
mentioning
confidence: 99%
“…This is of major importance to TN etiology and pathophysiology, and possibly also for selection of patients for microvascular decompression (MVD). However, approximately half of TN patients do not have a severe NVC on the symptomatic side (2)(3)(4)(5)(6). Furthermore, a simple NVC, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Intraoperative microneurographic recordings in trigeminal nerve fibers after stimulation of the known trigger zone in a TN patient demonstrated afterdischarges that were absent when unaffected facial areas were stimulated (13), loss, demyelination and dysmyelination consistent with NVC of the trigeminal nerve (2). However, recent studies have suggested that only severe neurovascular contact, causing displacement or atrophy of the nerve, is associated with pain in classical TN (3,4), and some studies have questioned whether NVC is necessary and sufficient for TN, since pain can occur and recur in the absence of nerve compression (5,6). A recent study reported…”
mentioning
confidence: 99%